School literacy movement program in elementary school, Indonesia: Literature review - Erlin Kartikasari; Endang Nuryasana (Intelektual Pustaka Media Utama, 2022)
The Ministry of Education and Culture developed the school literacy movement (SLM) program. This program aims to foster student interest in reading and improve reading skills so that knowledge can be mastered better. The author uses a literature review design by collecting data from various journal sources relevant to the SLM program in elementary schools, Indonesia. This research is an analytical descriptive study, which is a regular breakdown of the data that has been obtained, then understanding and explanation are given so that it can be understood well by the reader. The selected journal criteria are journals published in 2015-2021. SLM activities in elementary schools are influenced by supporting and inhibiting factors. The supporting factor is that the principal has a good commitment to carry out SLM activities, teachers and students and other components of the school also contribute to the success of SLM activities in elementary schools. Availability of sufficient funds to provide the necessary books is also a factor supporting SLM. While the inhibiting factor is that there are still very few books available so students cannot choose reading books that match their interests. Reading books is the main factor that must exist to make this SLM activity a success. Therefore, the procurement of reading books is very necessary. Students' reading habits are still low, they are still waiting for the teacher's orders to carry out SLM activities. The SLM schedule is not fully for 15-minute reading activities as specified in the manual. Lack of parental involvement in SLM activities.